The Effect of Cucumber Infused Water on Blood Pressure among Pre-Elderly Individuals with Hypertension in the Working Area of Babakan Sari Community Health Center, Bandung City - Sulistiyawati, Arie; Amalia, Irma Nur; Zahratunnisa, Cheila Azka (Journal of Social And Education Research, 2025)
The World Health Organization reports that approximately 1.13 billion people worldwide are living with hypertension, meaning that one in three individuals globally is diagnosed with this condition. In 2022, the number of people with hypertension in Bandung reached 706,051 cases. Hypertension management can be carried out through various non-pharmacological therapies, including bay leaf decoction, celery juice, ginger decoction, date infused water, lemon and watermelon infused water, and cucumber infused water. Cucumber infused water contains high levels of magnesium, calcium, potassium, and flavonoids, which may help reduce blood pressure. This study aimed to determine the effect of cucumber infused water on blood pressure among patients with hypertension at Babakan Sari Community Health Center. The study employed a pre-experimental (quasi-experimental) design using a one-group pretest–posttest approach. A total of 36 participants were included. The analysis showed a significant reduction in blood pressure after the administration of cucumber infused water, with a p-value less than ? = 0.05. A significant difference was observed in systolic blood pressure before and after the intervention (Z = ?5.324, p = 0.000), as well as in diastolic blood pressure (Z = ?5.362, p = 0.001). These results indicate that cucumber infused water has a significant effect on lowering blood pressure among pre-elderly patients with hypertension at Babakan Sari Community Health Center. This intervention is expected to be applied in daily life as an alternative non-pharmacological approach for hypertension management